Co(OH)2 Nanosheets Coupled With CNT Arrays Grown on Ni Mesh for High-Rate Asymmetric Supercapacitors with Excellent Capacitive Behavior. (10th September 2015) - Peng, Tianquan; Wang, Huanwen; Yi, Huan; Jing, Yuting; Sun, Peng; Wang, Xuefeng
Graphical abstract: Abstract: Aqueous asymmetric supercapacitors (ASCs) have been recently designed to improve energy storage density due to their large operation voltage and low cost. However, most reported ASCs (particularly for cobalt/nickel-based materials) always deviate from ideal capacitive behavior. In the present work, Co(OH)2 nanosheets arrays (NAs) are directly loaded on Ni mesh (Co(OH)2 NAs@Ni) via electrodeposition, while coral-like carbon nanotubes (CNTs) are successfully grown on Ni mesh (CNTs@Ni) through chemical vapor deposition (CVD). Using Co(OH)2 NAs@Ni as positive electrode and CNTs@Ni as negative electrode, a novel ASC has been successfully fabricated. Due to the merits of in-situ growth for active materials, the highly-conductive Ni mesh current collector and the positive synergistic effect between the positive and negative electrodes, our Co(OH)2 NAs@Ni//CNTs@Ni ASC exhibits excellent capacitive behavior, which is quite similar to RuO2 ·xH2 O-based supercapacitors. Notably, even when the scan rate rise up to 1 V s −1, the CV curve of the ASC device can still retains an inspiring quasi-rectangle shape from 0 to 1.5 V. Furthermore, the ASC demonstrates a high energy density of 19 Wh kg −1 at 113 W kg −1 . More impressively, an ultra-high power density of 45 kW kg −1 is achieved at an energy density of 12.5 Wh kg −1 . Besides, the Co(OH)2 NAs@Ni//CNTs@Ni ASC also presents long-term cycling stability (with only 4% capacitance loss after 7000 cycles).